Informing development of a socioeconomic data collection toolkit for marine energy: a literature review (Proceedings of the European Wave and Tidal Energy Conference, 2023)
Marine energy projects have the potential to create significant benefits by stimulating economic growth, improving local infrastructure and services, and providing energy security and resilience. Collecting social and economic data is necessary to anticipate potential benefits or adverse impacts, and to develop and appropriately site marine energy projects that suitably address community needs, incorporate and align with community values, and satisfy consenting requirements. Despite the importance of this information, consistent methodology for social and economic data collection to inform marine energy development is lacking. We review the literature from marine energy, other renewable energy industries, and relevant coastal sectors to identify common metrics, methods, and applicable tools for collecting data on social and economic effects. From this, we synthesize our findings and identify lessons learned that will form the foundations of a methods toolkit and template for data collection. This literature review and the eventual development of the toolkit will enable marine energy projects to identify, avoid, and mitigate potential negative effects at the forefront. By sharing findings from the literature and the lessons learned in the process of creating the toolkit, we hope to continue to advance the marine energy industry in a way that promotes energy equity, ensures environmental justice, and centers community values and needs.